ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI DESA PASIR JAYA TAHUN 2014 - Eka Yuli Handayani, Syafneli, (Jurnal Martenity and Neonatal, 2015)
Exclusive breastfeeding is breastfeeding (breast milk) as early as possible after delivery, provided without a schedule and not given any other food, although only water until the baby is 6 months old. In Indonesia, according to data from Susenas (National Socio-Economic Survey) coverage of exclusive breastfeeding in infants 6 months fell from 28.6% in 2007 to 24.3% in 2008. The aim of this study was known factors - factors related to breastfeeding exclusive in the village of Pasir Jaya Puskesmas Rambah Downstream II. The research method is analytic survey with cross sectional design. The way the sampling is done by sampling the saturated that all mothers with babies 6-12 months. Data collected by using a questionnaire distributed to mothers who breastfeed infants 6-12 months. This study data analysis using Chi Square test. On the degree of confidence (CI) 95% mothers gained knowledge factor p value = 0.389, employment status p value = 0.003, p value = 0.446 parity and age p value = 0.001. The conclusion from this study indicate that there is no significant relationship between knowledge of mother and parity of mothers with exclusive breastfeeding in the village of Pasir Jaya Puskesmas Rambah Downstream II in 2014 and no significant relationship between employment status and age of the mother with exclusive breastfeeding in the village Pasir Jaya Puskesmas Rambah Downstream II in 2014. Suggestions to the Midwife is expected to increase the IEC on age and employment status for nursing mothers, so mothers can give exclusive breastfeeding to their babies.Bibliography: 16 (2007-2013)